2001
DOI: 10.1046/j.1365-2230.2001.00842.x
|View full text |Cite
|
Sign up to set email alerts
|

Juvenile xanthogranuloma as a sequel to Langerhans cell histiocytosis: a report of three cases

Abstract: We report three children who had multisystem Langerhans cell histiocytosis (LCH) with cutaneous involvement and subsequently developed juvenile xanthogranuloma (JXG). JXG appeared 3--6 years after the initial manifestation of LCH. JXG lesions, which presented as yellowish papules, revealed typical Touton giant cells and were factor XIIIa positive but S100 and CD1a negative. Non-LCH histiocyte disorders, such as JXG, are known to occur as a reaction to a variety of external stimuli such as infection and trauma.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 14 publications
3
25
0
Order By: Relevance
“…Recently Hoeger et al [21]have reported 3 children with multisystem LCH who developed JXG 3–6 years after the initial manifestation of LCH, after many courses of chemotherapy. The authors hypothesized that the inflammatory reaction associated with LCH may precipitate the development of JXG.…”
Section: Commentmentioning
confidence: 99%
“…Recently Hoeger et al [21]have reported 3 children with multisystem LCH who developed JXG 3–6 years after the initial manifestation of LCH, after many courses of chemotherapy. The authors hypothesized that the inflammatory reaction associated with LCH may precipitate the development of JXG.…”
Section: Commentmentioning
confidence: 99%
“…These include JXG lesions occurring after LCH [48,49] and concurrent LCH and Erdheim-Chester Disease (ECD) or ECD following LCH [50], However, there have been no previous reports, to our knowledge, of concurrent LCH and JXG-family of lesions occurring in the thymus. Our 2 cases are both from young patients.…”
Section: Discussionmentioning
confidence: 99%
“…1,2,5,6,9,11,12,14,16,19 Moreover, the segregation of LCH from non-LCH is called into question when case reports appear that exhibit overlapping features of both conditions. 8,10,13,15,26 Depending on the timing of the biopsy, LCH can cytomorphologically resemble non-LCH and vice versa. For example, early lesions of XG are often devoid of TGC and lipid-laden histiocytes, and can even contain a few LC, whereas LC in older lesions of LCH often accumulate lipids.…”
Section: Discussionmentioning
confidence: 99%
“…For example, early lesions of XG are often devoid of TGC and lipid-laden histiocytes, and can even contain a few LC, whereas LC in older lesions of LCH often accumulate lipids. 8,15 Moreover, Birbeck granules, pathognomonic organelles of LC, are only identified in approximately half of LC in LCH. 8 Lastly, the S-100 and CD1a immunohistochemical stains routinely expressed by LC are occasionally expressed in non-LCH histiocytoses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation